A Significant Upregulation of miR-886-5p in High Grade and Invasive Bladder Tumors - Khoshnevisan, Atefeh; Parvin, Mahmoud; Ghorbanmehr, Nasim; Hatefi, Nasim; Galehdari, Hamid; Ziaee, Seyed Amir Mohsen; Mowla, Seyed Javad (Urology Journal, 2015)
Purpose: To investigate the expression alteration of miR-886-5p in bladder tumors and evaluating its expression level as a potential biomarker in this type of cancer. Materials and Methods: Formalin-fixed paraffin-embedded (FFPE) samples of bladder tumors belonging to 70 patients whom had been referred to the Shahid Labbafi-Nejad medical center were obtained from the archival collection of pathology department. After RNA extraction and cDNA synthesis, expression levels of miR-886-5p were quantified by a real-time reverse transcription polymerase chain reaction (RT-PCR) approach. Results: Our data revealed a significant upregulation ( 3 times) of miR-886-5p in high grade bladder tumors, compared to the low grade ones (P < .05). Moreover, its expression level could significantly discriminate noninvasive (Ta, T1) from invasive (T2-T4) tumor stages. Conclusion: Our data suggests a potential role for miR-886-5p in progression of bladder cancer.